Respuesta :
Answer:
Add the exponents and keep the same base Then find the reciprocal and change the sign of the exponent .
Step-by-step explanation:
Given the expression (2^3)(2^- 4), we will apply the law of indices below to solve the equation;
[tex]a^m \times a^n = a^{m+n}\\a^{-m} =\frac{1}{a^m}[/tex]
Applying this on the given expression;
[tex](2 ^ 3)(2 ^{-4})[/tex]
Step 1: Add the exponents and keep the same base as shown;
[tex]= (2 ^ 3)(2 ^{-4})\\\\= 2^{3+(-4)}\\\\ = 2^{3-4}\\\\= 2^{-1}[/tex]
Step 2: Find the reciprocal and change the sign of the exponent
[tex]= 2^{-1} \\= \frac{1}{2^1}\\= \frac{1}{2}[/tex]